2013
DOI: 10.22499/2.6301.010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of El Niño-Southern Oscillation in the ACCESS coupled model simulations for CMIP5

Abstract: One of the key performance measures for Coupled General Circulation Models (CGCMs) is their ability to realistically simulate the prominent modes of climate variability. Here, we investigate the realism of El Niño-Southern Oscillation (ENSO), the dominant mode of observed interannual climate variability, as simulated by the Australian Community Climate and Earth System Simulator (AC-CESS). We examine the key ENSO properties calculated from observations and from the pre-industrial control and historical simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 57 publications
1
28
0
Order By: Relevance
“…The ACCESS.1.0 model also captures the seasonal cycle relatively well (r = +0.75) whereas the ACCESS1.3 model performs relatively poorly (r = 0.23), a finding also reported by Rashid et al (2013). These differences are consistent with the findings of who found that CMIP5 models exhibited a clear improvement over CMIP3 models in simulating key ENSO features.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…The ACCESS.1.0 model also captures the seasonal cycle relatively well (r = +0.75) whereas the ACCESS1.3 model performs relatively poorly (r = 0.23), a finding also reported by Rashid et al (2013). These differences are consistent with the findings of who found that CMIP5 models exhibited a clear improvement over CMIP3 models in simulating key ENSO features.…”
Section: Resultssupporting
confidence: 86%
“…These differences are consistent with the findings of who found that CMIP5 models exhibited a clear improvement over CMIP3 models in simulating key ENSO features. Rashid et al (2013) also note that the ACCESS models simulate key ENSO better than most of the previous generation models.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…This assessment regarding equatorial SSTs is specific to PID, as Rashid et al (2013) found that ACCESS1.0 performed at least as well as ACCESS1.3 in simulating the ENSO cycle in the eastern Pacific, although with somewhat smaller amplitude than observed.…”
Section: Variability Assessment (Var)mentioning
confidence: 87%